Tax evasion, labor market effects, and income distribution - James Alm (IZA World of Labor, 2014)
To determine the full effects of taxation on income distribution, policymakers need to consider the impacts of tax evasion. In the standard analysis of tax evasion, all the benefits are assumed to accrue to tax evaders. But tax evasion has other impacts that determine its true effects. As factors of production move from tax-compliant to tax-evading (informal) sectors, changes in relative prices and productivity reduce incentives for workers to enter the informal sector. At least some of the gains from evasion are thus shifted to the consumers of the output of tax evaders, through lower prices.
Keywords: H26; C91; 330; tax evasion; tax incidence; general equilibrium